Malignant Eccrine Spiradenoma of the External Auditory Canal: A Case Report and Literature Review - You, Dong; Ma, Zhao; Liu, Jing; Song, Xiao; Dong, Wei (Frontiers in Oncology, 2021)
Spiradenocarcinoma, or malignant eccrine spiradenoma (MES), is a rare sweat gland tumour originating from eccrine sweat glands. To the best of our knowledge, only 2 cases of MES of the external auditory canal have been reported to date. Here, we report a third case of MES located in the external auditory canal.